2021
DOI: 10.3390/constrmater2010001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biochar on the Properties of Alkali-Activated Slag Pastes

Abstract: This paper examines the influence of biochar on the properties of alkali-activated slag pastes using two activator solutions, namely NaOH and Na2CO3. The biochar demonstrated different absorption kinetics in the mixture of slag and the two activator solutions. The pastes with biochar showed a delay in the heat flow peak, compared to the pastes without biochar, but the cumulative heat release in these pastes at later hours was increased, compared to the pastes without biochar. It was found that the use of bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…It is seen that the pastes with hydrogels showed a relatively shorter initial setting time, but their final setting time appeared to be increased compared to that of the paste without hydrogels, except in the case of the paste with H-d, which experienced a shorter final setting time. A prior investigation also demonstrated that AAS activated with NaOH and containing biochar as an internal curing agent had a longer final setting time compared to AAS without biochar with the same water/slag [ 58 ]. A possible reason for this behavior could be the lower availability of Na + in the pastes with hydrogels, as a portion of the activator solution is taken up by the hydrogels and is not readily accessible to the slag for reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It is seen that the pastes with hydrogels showed a relatively shorter initial setting time, but their final setting time appeared to be increased compared to that of the paste without hydrogels, except in the case of the paste with H-d, which experienced a shorter final setting time. A prior investigation also demonstrated that AAS activated with NaOH and containing biochar as an internal curing agent had a longer final setting time compared to AAS without biochar with the same water/slag [ 58 ]. A possible reason for this behavior could be the lower availability of Na + in the pastes with hydrogels, as a portion of the activator solution is taken up by the hydrogels and is not readily accessible to the slag for reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The autogenous shrinkage of AASF pastes is much higher than that of OPC pastes (Jensen and Hansen, 1999). The chemical shrinkage and finer pore structure are certainly responsible for the change in magnitude (Cartwright et al, 2014;Prabahar et al, 2021;Vafaei et al, 2020). For OPC, some swelling may be observed (as is the case for our mix) just after setting, while there is no swelling for the AASF.…”
Section: Autogenous Strainmentioning
confidence: 99%
“…The initial one corresponds to the early dissolution of the FA and BFS and occurs already during the mixing and is thus not recorded entirely (Fang et al, 2018;Prabahar et al, 2021;Vafaei et al, 2020). The second one corresponds to the acceleration of the formation of the C-N-A-S-H gel (Fang et al, 2018;Prabahar et al, 2021;Vafaei et al, 2020), the period in between is called "induction period" (Fang et al, 2018). Interestingly, the second peak occurs later (the induction period lasts longer) and is more pronounced for pastes with higher S/B and higher M s .…”
Section: Isothermal Calorimetrymentioning
confidence: 99%
See 2 more Smart Citations